Pengembangan Produk Kosmetika Berbahan Susu Kambing menjadi Sabun Cair - Uswatun Chasanah; Dyah Rahmasari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Goat's milk is rich in nutrients, especially vitamin A and lactic acid which are very beneficial for skin health, so it is suitable for liquid bath soap ingredients. However, well-known manufacturing takes a long time to make. Implemented training to producers of fresh goat's milk is formulating liquid soap made from fresh goat's milk that a simple method and quickly. The result of this activity is an increase in the knowledge and skills of participants so that they can enrich the variety of products based on fresh goat milk. It is hoped that with the increasing variety of goat milk products that they offer, there will be an increase in the economy of participants.